RETRACTED: Overexpression of microRNA-216a-3p Accelerates the Inflammatory Response in Cardiomyocytes in Type 2 Diabetes Mellitus by Targeting IFN-α2 - Liu, Xiaomeng; Zhang, Yusong; Liang, Hongwei; Xu, Yanchao (Frontiers in Endocrinology, 2020)
Background: Type 2 diabetes mellitus (T2DM) is a chronic, hyperglycemia-associated, metabolic disorder. Heart disease is a major complication of T2DM. The present study aimed to explore the effects of miR-216a-3p on cardiomyocyte proliferation, apoptosis, and inflammation in T2DM through the Toll-like receptor (TLR) pathway involving interferon-α2 (IFN-α2) mediation. Methods: T2DM was induced in rats by a high-fat diet, in combination with an intraperitoneal injection of low-dose streptozotocin. ELISA assays were conducted to measure inflammatory related factors in serum. Next, isolated cardiomyocytes were used in loss and gain of function experiments, followed by MTT and flow cytometry assays, conducted to evaluate cell proliferation, cell cycle, and apoptosis. Results: Our results revealed an increase in the inflammatory response in T2DM rat models, accompanied by significantly increased expression of miR-216a-3p and TLR pathway-related genes. However, a decrease in the expression of IFN-α2 was observed. Moreover, the presence of an miR-216a-3p inhibitor and si-IFN-α2, increased the expression of TLR pathway-related genes and cell apoptosis whereas cell proliferation was significantly decreased in the cardiomyocytes. Conclusion: We found that in T2DM, miR-216a-3p inhibited the proliferation and enhanced the apoptosis of cardiomyocytes and, generated an inflammatory response, through activation of the TLR pathway and targeting of IFN-α2.